S68 Understanding the pathological role of a genetic abnormality in DOCK3 in familial pulmonary fibrosis. (12th November 2019) - Kaur, R; Stewart, I; Jenkins, RG; John, A; Brown, D; Wain, L
Abstract : Idiopathic Pulmonary Fibrosis (IPF) is an uncommon but serious progressive fibrotic lung disease characterised by deteriorating symptoms, respiratory failure and death, often within 5 years from diagnosis. Up to 10% of patients with IPF have a family history of this disease, known as Familial Pulmonary Fibrosis (FPF). Prior genetic studies have identified rare variants in genes relating to telomere and epithelial function and are responsible for about 20% of FPF cases. To identify the missing heritability we recruited FPF patients to the 100k Genome Project and analysed data from the Whole Genome Sequencing from 169 cases (140 probands and 29 family members) and 8127 controls. Our filtering strategy identified rare deleterious variation (tier 1 and tier 2) in over 20% of the patients. Novel variants in over 20 genes, not previously associated with pulmonary fibrosis, were found to be present at much greater frequency in FPF patients compared with controls, including two missense exonic DOCK3 variants. DOCK3 is a member of the DOCK-B subfamily of guanine nucleotide exchange factors (GEFs) which function as activators of small G proteins. DOCK3 specifically activates the small G protein Rac and can promote reorganisation of the cytoskeleton and activation of downstream signalling pathways. Analysis of a number of lung tissue datasets has revealed lung tissue DOCK3 mRNA is increased in patients with pulmonary fibrosis. To determine whether DOCK3 protein is increased in whole lung tissue from patients with pulmonary fibrosis, immunohistochemical analysis was performed. In non-fibrotic lung tissue, a low level of DOCK3 expression was throughout the lung. In lung samples from IPF patients, DOCK3 was expressed widely in numerous cells within fibrotic areas of the lung although the exact cell types expressing DOCK3 in these regions have yet to be determined. These data suggest that DOCK3 could be a novel and important genetic contributor to fibrotic lung disease and studies to replicate these findings and define the functional consequences DOCK3 variants are ongoing. Acknowledgement: This research was made possible through access to the data and findings generated by the 100, 000 Genomes Project; http://www.genomicsengland.co.uk.